Croquis et photographies de la maison Balmain : quels enjeux patrimoniaux ? - Julia Guillon (In Situ)
This contribution sets out to reconsider the importance of the fashion heritage which is comprised of sketch and photo collections, the ‘related’ and complementary items alongside the fashion accessories and clothes themselves. It is based on the examination of these questions in the context of a specific French luxury fashion house, Balmain. Up to now, the collections in question were not familiar to the general public and have not been used very much in studies and exhibitions. This is in contrast with the accessories and items of clothing themselves, which paradoxically, often number no more than a few hundred pieces. The sketches and photos are better conserved than the clothing and represent thousands, or even tens of thousands of items. Their diffusion has of course become easier over the last decade or so thanks to digitization. Our objective in this article is to examine how these collections have come to be preserved in the house of Balmain, to underline the specific qualities of these archives and to imagine how they could be used. We show how their interpretation and promotion is a crucial question for creation, for corporate communication and for marketing and how they help rewrite the history of the Balmain house.